Duplex Stainless Steel
Patent Information
- Application Number
- JP2024536494
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-04-13
- Filing Date
- 2024-03-14
- Publication Date
- 2025-02-20
- Estimated Expiration
- 2044-03-14
Smart Images

Figure 0007633585000001 
Figure 0007633585000002 
Figure 0007633585000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to steel products, and more particularly to duplex stainless steel products. [Background technology]
[0002] Currently, the rise in carbon dioxide (CO2) concentrations on land has become a global problem. As a result, efforts to curb CO2 emissions are underway. Among these efforts to curb CO2 emissions, CCUS in particular has attracted attention.
[0003] CCUS is an abbreviation for Carbon dioxide Capture, Utilization and Storage. In other words, CCUS includes three technologies: capture, utilization, and storage of CO2. Of these, a technology that stores CO2 has been attracting attention, which captures CO2 emitted from industrial facilities such as power plants and factories and injects it into depleted oil wells for storage.
[0004] The steel materials used in this CO2 storage technology must have high strength because CO2 is injected into depleted oil wells. In addition, CO2 is a corrosive substance that corrodes steel. Therefore, the steel materials used in CO2 storage technology must have excellent corrosion resistance in a corrosive environment that contains a lot of CO2.
[0005] Duplex stainless steel materials having a two-phase structure of ferrite and austenite are known as steel materials having excellent corrosion resistance in corrosive environments. Duplex stainless steels are disclosed, for example, in Japanese Patent Laid-Open Nos. 5-132741 (Patent Document 1) and 9-195003 (Patent Document 2).
[0006] The duplex stainless steel material disclosed in Patent Document 1 has a chemical composition, in mass%, of C: 0.03% or less, Si: 1.0% or less, Mn: 1.5% or less, P: 0.040% or less, S: 0.008% or less, sol. Al: 0.040% or less, Ni: 5.0 to 9.0%, Cr: 23.0 to 27.0%, Mo: 2.0 to 4.0%, W: over 1.5 to 5.0%, N: 0.24 to 0.32%, with the balance being Fe and unavoidable impurities, and has a PREW (= Cr + 3.3 (Mo + 0.5W) + 16N) of 40 or more.
[0007] The duplex stainless steel material disclosed in Patent Document 2 contains, by mass%, C: 0.12% or less, Si: 1% or less, Mn: 2% or less, Ni: 3 to 12%, Cr: 20 to 35%, Mo: 0.5 to 10%, W: more than 3 to 8%, Co: 0.01 to 2%, Cu: 0.1 to 5%, N: 0.05 to 0.5%, and the balance being Fe and unavoidable impurities.
[0008] In the duplex stainless steel materials disclosed in Patent Documents 1 and 2, the corrosion resistance is improved by adjusting the chemical composition. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] Japanese Patent Application Publication No. 5-132741 [Patent Document 2] Japanese Patent Application Publication No. 9-195003 Summary of the Invention [Problem to be solved by the invention]
[0010] In the above-mentioned carbon dioxide storage technology, in order to inject CO2 into depleted oil wells, the CO2 to be injected into steel pipes is compressed and pressurized to make the CO2 supercritical. Meanwhile, the CO2 recovered from industrial facilities such as power plants and factories contains SOx and O2. Here, SOx is a general term for sulfur oxides represented by SO2. SOx dissolves in water to form acidic compounds (sulfuric acid, sulfurous acid, etc.), which cause general corrosion on the steel surface. In addition, O2 causes pitting corrosion. Therefore, supercritical CO2 containing SOx and O2 forms an extremely severe corrosive environment. In this specification, the corrosive environment formed by supercritical CO2 containing SOx and O2 is referred to as a "supercritical corrosive environment."
[0011] In other words, steel materials used in supercritical corrosion environments are required to have better general corrosion resistance and pitting corrosion resistance than those in conventional corrosive environments. The duplex stainless steel materials disclosed in Patent Documents 1 and 2 are not intended for use in such supercritical corrosion environments.
[0012] An object of the present disclosure is to provide a duplex stainless steel material having excellent general corrosion resistance and pitting corrosion resistance even in a supercritical corrosion environment. [Means for solving the problem]
[0013] The duplex stainless steel material according to the present disclosure comprises: In mass%, C: 0.050% or less, Si: 1.00% or less, Mn: 0.40-3.00%, P: 0.050% or less, S: 0.0050% or less, Cr: 20.00~24.50%, Cu: 0.10-3.00%, Ni: 2.00~10.00%, Mo: 0.80-5.00%, W: 0.01 to 1.50%, N: 0.001 to 0.350%, Co: 0.10-1.00%, Sn: 0.001 to 0.050%, Sol.Al: 0.050% or less, V: 0.01 to 0.50%, Ti: 0.001 to 0.050%, Ca: 0.0005~0.0100%, B: 0.0015~0.0050%, O: 0.010% or less, Mg: 0 to 0.010%, Rare earth elements: 0~0.010%, Zr: 0 to 0.010%, Nb: 0 to 0.500%, Ta: 0 to 0.100%, As: 0~0.050%, Zn: 0 to 0.010%, Pb: 0~0.010%, Sb: 0 to 0.010%, and the balance being Fe and impurities, Assuming that the content of each of the elements is within the above-mentioned range, Fn1 defined by formula (1) is 40.0 or more, In the duplex stainless steel material, Particles having an equivalent circle diameter of 1.0 μm or more, an Mn content of 10 mass% or more, and an S content of 10 mass% or more are defined as coarse Mn sulfides, When particles having a circle equivalent diameter of 2.0 μm or more, a Ca content of 20 mass% or more, an S content of 10 mass% or more, and a Mn content of less than 10 mass% are defined as coarse Ca sulfides, The total density of the coarse Mn sulfides and the coarse Ca sulfides is 0.50 particles / mm 2 is as follows: The microstructure of the duplex stainless steel material is composed of ferrite and austenite, The total number density of the coarse Mn sulfides and the coarse Ca sulfides in the ferrite is defined as NDA particles / mm 2 Define it as: The total number density of the coarse Mn sulfides and the coarse Ca sulfides in the austenite is defined as NDG particles / mm 2 When we define The NDA and the NDG satisfy the formula (2). Fn1=Cr+3.3(Mo+0.5W)+16N+2Ni+Cu+2Co+10Sn (1) NDA / NDG<0.50 (2) Here, the element symbols in formula (1) are substituted with the contents of the corresponding elements in mass %. Effect of the Invention
[0014] The duplex stainless steel material according to the present disclosure has excellent general corrosion resistance and pitting corrosion resistance even in supercritical corrosion environments. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present inventors have conducted a study on a duplex stainless steel material having excellent general corrosion resistance and pitting corrosion resistance in a supercritical corrosion environment formed by supercritical CO2 containing SOx and O2.
[0016] The present inventors first investigated, from the viewpoint of chemical composition, a steel material having excellent general corrosion resistance and excellent pitting corrosion resistance in a supercritical corrosion environment. The results were as follows: C: 0.050% or less, Si: 1.00% or less, Mn: 0.40-3.00%, P: 0.050% or less, S: 0.0050% or less, Cr: 20.00-24.50%, Cu: 0.10-3.00%, Ni: 2.00-10.00%, Mo: 0.80-5.00%, W: 0.01-1.50%, N: 0.001-0.350%, Co: 0.10-1.00%, Sn: 0.001-0.050%, sol.Al: 0.050% or less, V: 0.01-0.50%, Ti: 0.001-0.050%, C: 0.001-0.050%, It was considered that a steel material having a chemical composition of A: 0.0005-0.0100%, B: 0.0015-0.0050%, O: 0.010% or less, Mg: 0-0.010%, rare earth elements: 0-0.010%, Zr: 0-0.010%, Nb: 0-0.500%, Ta: 0-0.100%, As: 0-0.050%, Zn: 0-0.010%, Pb: 0-0.010%, Sb: 0-0.010%, and the balance being Fe and impurities, could potentially provide excellent general corrosion resistance and excellent pitting corrosion resistance in a supercritical corrosion environment.
[0017] On the other hand, even in the case of a duplex stainless steel material having the above-mentioned chemical composition, there are cases in which sufficient general corrosion resistance is not obtained in a supercritical corrosion environment. Therefore, the present inventors further investigated means for improving general corrosion resistance in a supercritical corrosion environment.
[0018] Specifically, the present inventors paid attention to the action of each element in the chemical composition. It has been known that, among the elements contained in the above-mentioned chemical composition, Cr, Mo, W, and N enhance the general corrosion resistance in a normal corrosive environment containing chlorides such as seawater. Therefore, the present inventors considered that these elements may enhance the general corrosion resistance even in a supercritical corrosion environment. The present inventors further investigated elements other than Cr, Mo, W, and N that enhance the general corrosion resistance in a supercritical corrosion environment. As a result, it was revealed that in a supercritical corrosion environment, not only Cr, Mo, W, and N, but also Ni, Cu, Co, and Sn enhance the general corrosion resistance of duplex stainless steel materials.
[0019] Therefore, the present inventors further investigated the relationship between the contents of Cr, Mo, W, N, Ni, Cu, Co and Sn in duplex stainless steel materials and general corrosion resistance in supercritical corrosion environments. As a result, it was found that in duplex stainless steel materials having the above-mentioned chemical composition, if Fn1 defined by formula (1) is 40.0 or more, general corrosion resistance in supercritical corrosion environments is improved. Fn1=Cr+3.3(Mo+0.5W)+16N+2Ni+Cu+2Co+10Sn (1) Here, the element symbols in formula (1) are substituted with the contents of the corresponding elements in mass %.
[0020] On the other hand, even in the case of a duplex stainless steel material having the above-mentioned chemical composition and satisfying Fn1 of 40.0 or more, in a supercritical corrosion environment, there are cases in which excellent pitting corrosion resistance is not sufficiently obtained. Therefore, the present inventors further investigated means for improving pitting corrosion resistance in a supercritical corrosion environment.
[0021] As mentioned above, supercritical corrosion environments contain not only high-temperature and high-pressure supercritical CO2 gas, but also SOx gas and O2 gas. SOx gas and O2 gas in supercritical corrosion environments are easily dissolved in water, making the environment more acidic. Therefore, in such supercritical corrosion environments, if inclusions are present on the surface layer of a duplex stainless steel material, the inclusions on the surface layer of the steel material are more likely to dissolve. If the inclusions dissolve, pits are formed on the surface. Furthermore, pits formed by dissolving coarse inclusions are likely to become the starting points of pitting corrosion in supercritical corrosion environments.
[0022] As a result of further investigations by the present inventors, it has become clear that in a supercritical corrosion environment, not all of the coarse inclusions (oxides, sulfides, nitrides, etc.) present on the surface layer of a duplex stainless steel material become the starting points of pitting corrosion, but coarse Mn sulfides and coarse Ca sulfides dissolve to form dents on the steel surface. In other words, if the number density of coarse Mn sulfides and coarse Ca sulfides can be reduced, the pitting corrosion resistance of a duplex stainless steel material having the above-mentioned chemical composition may be improved.
[0023] Specifically, the present inventors focused on Mn sulfides having an equivalent circle diameter of 1.0 μm or more and Ca sulfides having an equivalent circle diameter of 2.0 μm or more. Hereinafter, in this specification, particles having a Mn content of 10 mass% or more and a S content of 10 mass% or more are also referred to as Mn sulfides. Similarly, in this specification, particles having a Ca content of 20 mass% or more, a S content of 10 mass% or more, and a Mn content of less than 10 mass% are also referred to as Ca sulfides. Furthermore, in this specification, Mn sulfides having an equivalent circle diameter of 1.0 μm or more are also referred to as "coarse Mn sulfides". Similarly, in this specification, Ca sulfides having an equivalent circle diameter of 2.0 μm or more are also referred to as "coarse Ca sulfides". In this specification, coarse Mn sulfides and coarse Ca sulfides are also collectively referred to as "specific inclusions".
[0024] The present inventors considered that if the formation of large coarse Mn sulfides as well as large Ca sulfides could be suppressed, the pitting corrosion resistance of the duplex stainless steel material having the above-mentioned chemical composition could be improved. Specifically, when the total number density of specific inclusions (coarse Mn sulfides and coarse Ca sulfides) is 0.50 pieces / mm 2 It was thought that, if the chemical composition of the duplex stainless steel material described above is as follows, excellent pitting corrosion resistance can be obtained.
[0025] On the other hand, if the above chemical composition is satisfied and Fn1 is 40.0 End and the total density of specific inclusions is 0.50 pieces / mm 2 Even when the temperature is below 100° C., there are cases where excellent pitting corrosion resistance is not obtained. Therefore, the present inventors conducted a detailed investigation into cases where excellent pitting corrosion resistance is not obtained, and investigated means for improving pitting corrosion resistance. As a result, it was found that when excellent pitting corrosion resistance is not obtained, pitting corrosion is likely to occur in the ferrite of the microstructure of the duplex stainless steel material.
[0026] Here, the duplex stainless steel material having the above-mentioned chemical composition has a microstructure consisting of ferrite and austenite. In this specification, "consisting of ferrite and austenite" means that phases other than ferrite and austenite are negligibly small. In addition, between ferrite and austenite, austenite has better corrosion resistance than ferrite. Therefore, in the duplex stainless steel material having the above-mentioned chemical composition, there is a concern that pitting corrosion may occur selectively in the ferrite. Therefore, the present inventors thought that if the specific inclusions in the duplex stainless steel material could be unevenly distributed in the austenite, it may be possible to suppress the occurrence of selective pitting corrosion in the ferrite.
[0027] As a result of detailed investigations by the present inventors based on the above findings, it was found that the above-mentioned chemical composition is satisfied and Fn1 is 40.0 End The total density of specific inclusions is 0.50 pieces / mm 2 After reducing the total number density NDA (pieces / mm 2 ) and the total number density of specific inclusions in austenite (NDG (pieces / mm 2 ) satisfies formula (2), excellent general corrosion resistance and pitting corrosion resistance can be obtained even in a supercritical corrosion environment. NDA / NDG<0.50 (2)
[0028] Fn2 is defined as NDA / NDG. Fn2 is an index showing the extent to which specific inclusions (coarse Mn sulfides and coarse Ca sulfides) are present in ferrite. If Fn2 is less than 0.50, the number density of the specific inclusions in ferrite can be sufficiently reduced. As a result, the occurrence of selective pitting corrosion in ferrite can be suppressed, provided that the other configurations of this embodiment are satisfied. On the other hand, if Fn2 is 0.50 or more, the ferrite contains a large number of specific inclusions, and there is a concern that selective pitting corrosion will occur.
[0029] Therefore, the duplex stainless steel material according to the present embodiment has the above-mentioned chemical composition, Fn1 is 40.0 or more, and the total number density of specific inclusions is 0.50 pieces / mm2 or less, and further, Fn2 is made less than 0.50. As a result, the duplex stainless steel material according to this embodiment has excellent general corrosion resistance and pitting corrosion resistance even in a supercritical corrosion environment.
[0030] The gist of the duplex stainless steel material according to this embodiment, which was completed based on the above findings, is as follows.
[0031] [1] A duplex stainless steel material, In mass%, C: 0.050% or less, Si: 1.00% or less, Mn: 0.40-3.00%, P: 0.050% or less, S: 0.0050% or less, Cr: 20.00~24.50%, Cu: 0.10-3.00%, Ni: 2.00~10.00%, Mo: 0.80-5.00%, W: 0.01 to 1.50%, N: 0.001 to 0.350%, Co: 0.10-1.00%, Sn: 0.001 to 0.050%, Sol.Al: 0.050% or less, V: 0.01 to 0.50%, Ti: 0.001 to 0.050%, Ca: 0.0005~0.0100%, B: 0.0015~0.0050%, O: 0.010% or less, Mg: 0 to 0.010%, Rare earth elements: 0~0.010%, Zr: 0 to 0.010%, Nb: 0 to 0.500%, Ta: 0 to 0.100%, As: 0~0.050%, Zn: 0 to 0.010%, Pb: 0~0.010%, Sb: 0 to 0.010%, and the balance being Fe and impurities, Assuming that the content of each of the elements is within the above-mentioned range, Fn1 defined by formula (1) is 40.0 or more, In the duplex stainless steel material, Particles having an equivalent circle diameter of 1.0 μm or more, an Mn content of 10 mass% or more, and an S content of 10 mass% or more are defined as coarse Mn sulfides, When particles having a circle equivalent diameter of 2.0 μm or more, a Ca content of 20 mass% or more, an S content of 10 mass% or more, and a Mn content of less than 10 mass% are defined as coarse Ca sulfides, The total density of the coarse Mn sulfides and the coarse Ca sulfides is 0.50 particles / mm 2 is as follows: The microstructure of the duplex stainless steel material is composed of ferrite and austenite, The total number density of the coarse Mn sulfides and the coarse Ca sulfides in the ferrite is defined as NDA particles / mm 2 Define it as: The total number density of the coarse Mn sulfides and the coarse Ca sulfides in the austenite is defined as NDG particles / mm 2 When we define The NDA and the NDG satisfy formula (2), Duplex stainless steel material. Fn1=Cr+3.3(Mo+0.5W)+16N+2Ni+Cu+2Co+10Sn (1) NDA / NDG<0.50 (2) Here, the element symbols in formula (1) are substituted with the contents of the corresponding elements in mass %.
[0032] [2] [1] A duplex stainless steel material according to the present invention, Mg: 0.001 to 0.010%, Rare earth elements: 0.001~0.010%, Zr: 0.001 to 0.010%, Nb: 0.001 to 0.500%, Ta: 0.001 to 0.100%, As: 0.001 to 0.050%, Zn: 0.001 to 0.010%, Pb: 0.001 to 0.010%, and Sb: 0.001 to 0.010%, containing one or more elements selected from the group consisting of Duplex stainless steel material.
[0033] [3] The duplex stainless steel material according to [1] or [2], The duplex stainless steel material is a steel pipe. Duplex stainless steel material.
[0034] The shape of the duplex stainless steel material according to this embodiment is not particularly limited. The duplex stainless steel material according to this embodiment may be a steel pipe, a round bar (solid material), or a steel plate. The round bar means a steel bar having a circular cross section perpendicular to the axial direction. The steel pipe may be a seamless steel pipe or a welded steel pipe.
[0035] The duplex stainless steel material according to this embodiment will be described in detail below.
[0036] [Chemical composition] The chemical composition of the duplex stainless steel material according to this embodiment contains the following elements: "%" for each element means mass % unless otherwise specified.
[0037] C: 0.050% or less Carbon (C) is inevitably contained. That is, the lower limit of the C content is more than 0%. C forms Cr carbides at the grain boundaries and increases the corrosion sensitivity at the grain boundaries. Therefore, if the C content is too high, the corrosion resistance of the steel material decreases even if the contents of other elements are within the range of this embodiment. Therefore, the C content is 0.050% or less. The preferred upper limit of the C content is 0.048%, more preferably 0.045%. The C content is preferably as low as possible. However, an extreme reduction in the C content significantly increases the manufacturing cost. Therefore, in consideration of industrial production, the preferred lower limit of the C content is 0.001%, more preferably 0.003%, and even more preferably 0.005%.
[0038] Si: 1.00% or less Silicon (Si) is inevitably contained. That is, the lower limit of the Si content is more than 0%. Si deoxidizes steel. On the other hand, if the Si content is too high, the toughness of the steel material decreases even if the contents of other elements are within the range of this embodiment. Therefore, the Si content is 1.00% or less. A preferred upper limit of the Si content is 0.90%, more preferably 0.80%, and even more preferably 0.70%. A preferred lower limit of the Si content for more effectively obtaining the above effects is 0.01%, more preferably 0.05%, more preferably 0.10%, and even more preferably 0.20%.
[0039] Mn: 0.40-3.00% Manganese (Mn) deoxidizes and desulfurizes steel. Mn also improves the hot workability of steel. If the Mn content is too low, the above effects cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, Mn combines with sulfur (S) to form Mn sulfides. Therefore, if the Mn content is too high, even if the contents of other elements are within the range of this embodiment, a large number of coarse Mn sulfides are formed, and the pitting corrosion resistance of the steel in a supercritical corrosion environment decreases. Therefore, the Mn content is 0.40 to 3.00%. The preferable lower limit of the Mn content is 0.50%, and more preferably 0.60%. The preferable upper limit of the Mn content is 2.90%, and more preferably 2.70%.
[0040] P:0.050% or less Phosphorus (P) is unavoidably contained. That is, the lower limit of the P content is more than 0%. P segregates at grain boundaries. Therefore, if the P content is too high, the corrosion resistance of the steel material decreases even if the contents of other elements are within the range of this embodiment. Therefore, the P content is 0.050% or less. The preferred upper limit of the P content is 0.045%, more preferably 0.040%, and even more preferably 0.030%. The P content is preferably as low as possible. However, an extreme reduction in the P content significantly increases the manufacturing cost. Therefore, in consideration of industrial production, the preferred lower limit of the P content is 0.001%, and even more preferably 0.003%.
[0041] S: 0.0050% or less Sulfur (S) is inevitably contained. That is, the lower limit of the S content is more than 0%. S segregates at grain boundaries. Therefore, if the S content is too high, the corrosion resistance of the steel material decreases even if the contents of other elements are within the range of this embodiment. Therefore, the S content is 0.0050% or less. The preferred upper limit of the S content is 0.0040%, more preferably 0.0030%, and even more preferably 0.0020%. The S content is preferably as low as possible. However, an extreme reduction in the S content significantly increases the manufacturing cost. Therefore, in consideration of industrial production, the preferred lower limit of the S content is 0.0001%, more preferably 0.0003%, and even more preferably 0.0005%.
[0042] Cr: 20.00~24.50% Chromium (Cr) forms a passive film as an oxide on the surface of a steel material, and enhances the general corrosion resistance and pitting corrosion resistance of the steel material in a supercritical corrosion environment. If the Cr content is too low, the above effects cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Cr content is too high, the hot workability of the steel material decreases even if the contents of other elements are within the range of this embodiment. Therefore, the Cr content is 20.00 to 24.50%. The preferred lower limit of the Cr content is 20.20%, more preferably 20.50%, and even more preferably 21.00%. The preferred upper limit of the Cr content is 24.30%, more preferably 24.00%, and even more preferably 23.80%.
[0043] Cu: 0.10-3.00% Copper (Cu) enhances the general corrosion resistance of steel in a supercritical corrosion environment. If the Cu content is too low, the above effect cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Cu content is too high, the hot workability of the steel decreases even if the contents of other elements are within the range of this embodiment. Therefore, the Cu content is 0.10 to 3.00%. The preferred lower limit of the Cu content is 0.15%, more preferably 0.20%, and even more preferably 0.25%. The preferred upper limit of the Cu content is 2.90%, more preferably 2.75%, and even more preferably 2.50%.
[0044] Ni: 2.00~10.00% Nickel (Ni) stabilizes the austenite of the steel material. Ni also enhances the general corrosion resistance of the steel material in a supercritical corrosion environment. If the Ni content is too low, the above effects cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Ni content is too high, the volume fraction of austenite becomes too high even if the contents of other elements are within the range of this embodiment, and the yield strength of the steel material decreases. Therefore, the Ni content is 2.00 to 10.00%. The preferred lower limit of the Ni content is 2.50%, more preferably 3.00%, more preferably 3.50%, and more preferably 4.00%. The preferred upper limit of the Ni content is 9.80%, more preferably 9.60%, more preferably 9.30%, and more preferably 9.00%.
[0045] Mo: 0.80~5.00% Molybdenum (Mo) enhances the general corrosion resistance of steel in a supercritical corrosion environment. If the Mo content is too low, the above effect cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Mo content is too high, the hot workability of the steel decreases even if the contents of other elements are within the range of this embodiment. Therefore, the Mo content is 0.80 to 5.00%. The preferred lower limit of the Mo content is 0.85%, more preferably 1.00%, and even more preferably 1.50%. The preferred upper limit of the Mo content is 4.80%, more preferably 4.50%, and even more preferably 4.30%.
[0046] W: 0.01 to 1.50% Tungsten (W) enhances the general corrosion resistance of steel in a supercritical corrosion environment. If the W content is too low, the above effect cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the W content is too high, the toughness of the steel decreases even if the contents of other elements are within the range of this embodiment. Therefore, the W content is 0.01 to 1.50%. The preferred lower limit of the W content is 0.05%, more preferably 0.07%, more preferably 0.10%, and more preferably 0.15%. The preferred upper limit of the W content is 1.45%, more preferably 1.35%, and more preferably 1.25%.
[0047] N: 0.001 to 0.350% Nitrogen (N) stabilizes the austenite of the steel material. N also enhances the general corrosion resistance of the steel material in a supercritical corrosion environment. If the N content is too low, the above effects cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the N content is too high, the hot workability of the steel material decreases even if the contents of other elements are within the range of this embodiment. Therefore, the N content is 0.001 to 0.350%. The preferred lower limit of the N content is 0.003%, more preferably 0.005%, and even more preferably 0.010%. The preferred upper limit of the N content is 0.345%, and even more preferably 0.340%.
[0048] Co: 0.10-1.00% Cobalt (Co) forms a coating on the surface of a steel material to enhance the general corrosion resistance and pitting corrosion resistance of the steel material in a supercritical corrosion environment. If the Co content is too low, the above effects cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Co content is too high, the manufacturing cost increases significantly even if the contents of other elements are within the range of this embodiment. Therefore, the Co content is 0.10 to 1.00%. The preferred lower limit of the Co content is 0.11%, more preferably 0.12%, and more preferably 0.15%. The preferred upper limit of the Co content is 0.95%, more preferably 0.90%, and more preferably 0.80%.
[0049] Sn: 0.001 to 0.050% Tin (Sn) enhances the general corrosion resistance and pitting corrosion resistance of steel in a supercritical corrosion environment. If the Sn content is too low, the above effects cannot be sufficiently obtained even if the contents of other elements are within the ranges of this embodiment. On the other hand, if the Sn content is too high, the hot workability of the steel decreases even if the contents of other elements are within the ranges of this embodiment. Therefore, the Sn content is 0.001 to 0.050%. The preferred lower limit of the Sn content is 0.002%, more preferably 0.003%, and more preferably 0.005%. The preferred upper limit of the Sn content is 0.045%, more preferably 0.040%, and more preferably 0.035%.
[0050] Sol.Al: 0.050% or less Aluminum (Al) is inevitably contained. That is, the lower limit of the Al content is more than 0%. Al deoxidizes the steel. On the other hand, if the Al content is too high, even if the contents of other elements are within the range of this embodiment, coarse oxide-based inclusions are generated, and the toughness of the steel material decreases. Therefore, the Al content is 0.050% or less. The preferred lower limit of the Al content is 0.001%, more preferably 0.005%, and even more preferably 0.010%. The preferred upper limit of the Al content is 0.045%, and even more preferably 0.040%. The Al content in this specification means the content of "acid-soluble Al", that is, sol.Al.
[0051] V: 0.01 to 0.50% Vanadium (V) increases the strength of steel material. If the V content is too low, the above effect cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the V content is too high, the strength of the steel material becomes too high and the toughness of the steel material decreases even if the contents of other elements are within the range of this embodiment. Therefore, the V content is 0.01 to 0.50%. The preferred lower limit of the V content is 0.02%, more preferably 0.03%, more preferably 0.05%, and more preferably 0.10%. The preferred upper limit of the V content is 0.45%, more preferably 0.40%, and more preferably 0.30%.
[0052] Ti: 0.001 to 0.050% Titanium (Ti) forms carbonitrides and increases the strength of steel. If the Ti content is too low, the above effects cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Ti content is too high, the strength of the steel becomes too high and the toughness of the steel decreases even if the contents of other elements are within the range of this embodiment. Therefore, the Ti content is 0.001 to 0.050%. The preferred lower limit of the Ti content is 0.002%, more preferably 0.003%, and more preferably 0.005%. The preferred upper limit of the Ti content is 0.045%, more preferably 0.040%, more preferably 0.030%, more preferably 0.025%, and more preferably 0.020%.
[0053] Ca: 0.0005~0.0100% Calcium (Ca) combines with S in the steel material to generate Ca sulfides and suppress the generation of coarse Mn sulfides. As a result, the number density of coarse Mn sulfides in the steel material is reduced, and the pitting corrosion resistance of the steel material in a supercritical corrosion environment is improved. If the Ca content is too low, the above effect cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Ca content is too high, a large number of coarse Ca sulfides are formed even if the contents of other elements are within the range of this embodiment, and the pitting corrosion resistance of the steel material in a supercritical corrosion environment is reduced. Therefore, the Ca content is 0.0005 to 0.0100%. The preferred lower limit of the Ca content is 0.0006%, more preferably 0.0007%, and more preferably 0.0008%. The preferred upper limit of the Ca content is 0.0090%, more preferably 0.0080%, more preferably 0.0060%, and more preferably 0.0050%.
[0054] B: 0.0015~0.0050% Boron (B) suppresses segregation of S in steel to grain boundaries and improves the hot workability of the steel. If the B content is too low, the above effects cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the B content is too high, boron nitride (BN) is generated, even if the contents of other elements are within the range of this embodiment, and the toughness of the steel is reduced. Therefore, the B content is 0.0015 to 0.0050%. The preferred lower limit of the B content is 0.0018%, more preferably 0.0020%, and more preferably 0.0025%. The preferred upper limit of the B content is 0.0045%, more preferably 0.0040%, and more preferably 0.0035%.
[0055] O: 0.010% or less Oxygen (O) is inevitably contained. That is, the lower limit of the O content is more than 0%. O forms oxides and reduces the toughness of the steel material. Therefore, if the O content is too high, the corrosion resistance of the steel material decreases even if the contents of other elements are within the range of this embodiment. Therefore, the O content is 0.010% or less. A preferred upper limit of the O content is 0.009%, more preferably 0.008%, and even more preferably 0.007%. The O content is preferably as low as possible. However, an extreme reduction in the O content significantly increases the manufacturing cost. Therefore, in consideration of industrial production, a preferred lower limit of the O content is 0.001%, and even more preferably 0.003%.
[0056] The balance of the chemical composition of the duplex stainless steel material according to the present embodiment is composed of Fe and impurities. Here, the impurities in the chemical composition refer to substances that are mixed in from raw materials such as ore and scrap, or the manufacturing environment, during industrial production of the duplex stainless steel material, and are permissible within a range that does not adversely affect the duplex stainless steel material according to the present embodiment.
[0057] [Optional element] The chemical composition of the duplex stainless steel material according to the present embodiment may further contain one or more elements selected from the group consisting of Mg and rare earth elements in place of a portion of Fe. All of these elements are optional elements and improve the hot workability of the steel material.
[0058] Magnesium: 0 to 0.010% Magnesium (Mg) is an optional element and may not be contained. That is, the Mg content may be 0%. When contained, Mg fixes S in the steel material as sulfides to render it harmless, and improves the hot workability of the steel material. If even a small amount of Mg is contained, the above effect can be obtained to some extent. However, if the Mg content is too high, even if the contents of other elements are within the range of this embodiment, the oxides in the steel material become coarse, and the toughness of the steel material decreases. Therefore, the Mg content is 0 to 0.010%. The preferable lower limit of the Mg content is more than 0%, more preferably 0.001%, more preferably 0.002%, and more preferably 0.003%. The preferable upper limit of the Mg content is 0.009%, and more preferably 0.008%.
[0059] Rare earth elements: 0~0.010% Rare earth elements (REM) are optional elements and may not be contained. That is, the REM content may be 0%. When contained, REM fixes S in the steel material as sulfides to render it harmless, and improves the hot workability of the steel material. The above effect can be obtained to some extent if even a small amount of REM is contained. However, if the REM content is too high, even if the contents of other elements are within the range of this embodiment, the oxides in the steel material become coarse, and the toughness of the steel material decreases. Therefore, the REM content is 0 to 0.010%. The preferable lower limit of the REM content is more than 0%, more preferably 0.001%, more preferably 0.002%, and more preferably 0.003%. The preferable upper limit of the REM content is 0.009%, and more preferably 0.008%.
[0060] In this specification, REM refers to one or more elements selected from the group consisting of scandium (Sc) with atomic number 21, yttrium (Y) with atomic number 39, and the lanthanides lanthanum (La) with atomic number 57 to lutetium (Lu) with atomic number 71. In addition, in this specification, the REM content refers to the total content of these elements.
[0061] The chemical composition of the duplex stainless steel material according to the present embodiment may further contain one or more elements selected from the group consisting of Zr, Nb, and Ta in place of a portion of Fe. All of these elements are optional elements and increase the strength of the steel material.
[0062] Zr: 0 to 0.010% Zirconium (Zr) is an optional element and may not be contained. That is, the Zr content may be 0%. When contained, Zr forms carbonitrides and increases the strength of the steel material. If even a small amount of Zr is contained, the above effect can be obtained to some extent. However, if the Zr content is too high, even if the contents of other elements are within the range of this embodiment, the strength of the steel material becomes too high and the toughness of the steel material decreases. Therefore, the Zr content is 0 to 0.010%. The preferable lower limit of the Zr content is more than 0%, more preferably 0.001%, more preferably 0.002%, and more preferably 0.003%. The preferable upper limit of the Zr content is 0.009%, and more preferably 0.008%.
[0063] Nb: 0 to 0.500% Niobium (Nb) is an optional element and may not be contained. That is, the Nb content may be 0%. When contained, Nb forms carbonitrides and increases the strength of the steel material. If even a small amount of Nb is contained, the above effect can be obtained to some extent. However, if the Nb content is too high, even if the contents of other elements are within the range of this embodiment, the strength of the steel material becomes too high and the toughness of the steel material decreases. Therefore, the Nb content is 0 to 0.500%. The preferred lower limit of the Nb content is more than 0%, more preferably 0.001%, more preferably 0.005%, more preferably 0.010%, and more preferably 0.050%. The preferred upper limit of the Nb content is 0.400%, more preferably 0.300%, and more preferably 0.200%.
[0064] Ta: 0 to 0.100% Tantalum (Ta) is an optional element and may not be contained. That is, the Ta content may be 0%. When contained, Ta forms carbonitrides and increases the strength of the steel material. If even a small amount of Ta is contained, the above effect can be obtained to some extent. However, if the Ta content is too high, even if the contents of other elements are within the range of this embodiment, the strength of the steel material becomes too high and the toughness of the steel material decreases. Therefore, the Ta content is 0 to 0.100%. The preferred lower limit of the Ta content is more than 0%, more preferably 0.001%, more preferably 0.002%, more preferably 0.003%, and more preferably 0.005%. The preferred upper limit of the Ta content is 0.095%, more preferably 0.090%, and more preferably 0.080%.
[0065] The chemical composition of the duplex stainless steel material according to the present embodiment may further contain one or more elements selected from the group consisting of As, Zn, Pb, and Sb in place of a portion of Fe. All of these elements are optional elements, and enhance the corrosion resistance of the steel material.
[0066] As: 0 to 0.050% Arsenic (As) is an optional element and may not be contained. That is, the As content may be 0%. When contained, As enhances the general corrosion resistance of the steel material in a supercritical corrosion environment. If even a small amount of As is contained, the above effect can be obtained to a certain extent. However, if the As content is too high, even if the contents of other elements are within the range of this embodiment, the general corrosion resistance and pitting corrosion resistance of the steel material in a supercritical corrosion environment may be reduced. Therefore, the As content is 0 to 0.050%. The preferred lower limit of the As content is more than 0%, more preferably 0.001%, and more preferably 0.002%. The preferred upper limit of the As content is 0.045%, more preferably 0.040%, and more preferably 0.035%.
[0067] Zn: 0 to 0.010% Zinc (Zn) is an optional element and may not be contained. That is, the Zn content may be 0%. When contained, Zn enhances the general corrosion resistance of the steel material in a supercritical corrosion environment. If even a small amount of Zn is contained, the above effect can be obtained to a certain extent. However, if the Zn content is too high, even if the contents of other elements are within the range of this embodiment, the general corrosion resistance and pitting corrosion resistance of the steel material in a supercritical corrosion environment may be reduced. Therefore, the Zn content is 0 to 0.010%. The preferred lower limit of the Zn content is more than 0%, more preferably 0.001%, more preferably 0.002%, and more preferably 0.003%. The preferred upper limit of the Zn content is 0.009%, more preferably 0.008%, and more preferably 0.007%.
[0068] Pb: 0~0.010% Lead (Pb) is an optional element and may not be contained. That is, the Pb content may be 0%. When contained, Pb enhances the general corrosion resistance of the steel material in a supercritical corrosion environment. If even a small amount of Pb is contained, the above effect can be obtained to a certain extent. However, if the Pb content is too high, many scratches will occur on the steel material surface after hot working even if the contents of other elements are within the range of this embodiment. Therefore, the Pb content is 0 to 0.010%. The preferred lower limit of the Pb content is more than 0%, more preferably 0.001%, more preferably 0.002%, and more preferably 0.003%. The preferred upper limit of the Pb content is 0.009%, more preferably 0.008%, and more preferably 0.007%.
[0069] Sb: 0 to 0.010% Antimony (Sb) is an optional element and may not be contained. That is, the Sb content may be 0%. When contained, Sb enhances the general corrosion resistance of the steel material in a supercritical corrosion environment. If even a small amount of Sb is contained, the above effect can be obtained to a certain extent. However, if the Sb content is too high, even if the contents of other elements are within the range of this embodiment, the manufacturing cost will increase extremely. Therefore, the Sb content is 0 to 0.010%. The preferred lower limit of the Sb content is more than 0%, more preferably 0.001%, more preferably 0.002%, and more preferably 0.003%. The preferred upper limit of the Sb content is 0.009%, and more preferably 0.008%.
[0070] [Fn1] The duplex stainless steel material according to this embodiment has Fn1, defined by formula (1), of 40.0 or more, provided that the content of each element in the chemical composition is within the above-mentioned range. Fn1=Cr+3.3(Mo+0.5W)+16N+2Ni+Cu+2Co+10Sn (1) Here, the element symbols in formula (1) are substituted with the contents in mass % of the corresponding elements.
[0071] Fn1 is an index of the general corrosion resistance of a duplex stainless steel material in a supercritical corrosion environment. As described above, in a supercritical corrosion environment in which supercritical CO2 gas contains SOx gas and O2 gas, among the elements of the above-mentioned chemical composition, not only Cr, Mo, W, and N but also Ni, Cu, Co, and Sn contribute to improving the general corrosion resistance. In other words, Fn1 is a parameter formula set in consideration of the contribution of each element to the general corrosion resistance in a supercritical corrosion environment in a duplex stainless steel material having the above-mentioned chemical composition. In a duplex stainless steel material having the above-mentioned chemical composition, if Fn1 is 40.0 or more, the general corrosion resistance in a supercritical corrosion environment is significantly improved. Therefore, in this embodiment, Fn1 is 40.0 or more.
[0072] The preferred lower limit of Fn1 is 40.5, more preferably 41.0, more preferably 41.5, and more preferably 42.0. The upper limit of Fn1 is not particularly limited, but is substantially 74.6. The upper limit of Fn1 may be 70.0, 68.0, or 65.0. Fn1 is calculated by rounding off the first decimal place of the obtained numerical value.
[0073] [Total number density of specific inclusions] The duplex stainless steel material according to the present embodiment has the above-mentioned chemical composition, Fn1 is 40.0 or more, and the total number density of specific inclusions is 0.50 pieces / mm 2 In this specification, the specific inclusions are a collective term for particles (coarse Mn sulfides) having an equivalent circle diameter of 1.0 μm or more, and containing, among the specified elements identified by the method described below, a Mn content of 10 mass% or more and a S content of 10 mass% or more, and particles (coarse Ca sulfides) having an equivalent circle diameter of 2.0 μm or more, and containing, among the specified elements identified by the method described below, a Ca content of 20 mass% or more, a S content of 10 mass% or more, and a Mn content of less than 10 mass%.
[0074] In this specification, unit area (1 mm 2 The sum of the number densities of coarse Mn sulfides and coarse Ca sulfides per unit area was calculated as the total number density of specific inclusions (units / mm2 Hereinafter, the total number density of specific inclusions is also referred to as the total number density ND (Number Density) of specific inclusions.
[0075] As described above, in a supercritical corrosion environment, inclusions in the surface layer of a steel material are likely to dissolve, and specific inclusions (coarse Mn sulfides and coarse Ca sulfides) are likely to become the starting points of pitting corrosion. Therefore, in this embodiment, the total number density ND of the specific inclusions is set to 0.50 pieces / mm 2 As a result, provided that the other configurations of this embodiment are satisfied, the duplex stainless steel material has excellent general corrosion resistance and pitting corrosion resistance even in a supercritical corrosion environment.
[0076] The preferred upper limit of the total number density ND of specific inclusions is 0.49 pieces / mm 2 and more preferably 0.48 pieces / mm 2 and more preferably 0.45 pieces / mm 2 The lower limit of the total number density ND of the specific inclusions is not particularly limited, and is 0.00 pieces / mm 2 In the duplex stainless steel material according to the present embodiment, the lower limit of the total number density ND of the specific inclusions may be, for example, 0.01 pieces / mm 2 may be 0.05 pieces / mm 2 may be 0.10 pieces / mm 2 may be 0.15 pieces / mm 2 The method for determining the total number density ND of the specific inclusions will be described later.
[0077] [Microstructure] The microstructure of the duplex stainless steel material according to the present embodiment is composed of ferrite and austenite. In this specification, "composed of ferrite and austenite" means that phases other than ferrite and austenite are negligibly small. For example, the volume fraction of precipitates and inclusions in the microstructure of the duplex stainless steel material according to the present embodiment is negligibly low compared to the volume fraction of ferrite and austenite. In other words, the microstructure of the duplex stainless steel material according to the present embodiment may contain minute amounts of precipitates, inclusions, etc. in addition to ferrite and austenite.
[0078] In the microstructure of the duplex stainless steel material according to the present embodiment, the volume fractions of ferrite and austenite are not particularly limited. However, in the microstructure of the duplex stainless steel material according to the present embodiment having the above-mentioned chemical composition, the volume fraction of ferrite may be, for example, 35 to 65%. In this case, the volume fraction of austenite is 35 to 65%. The method of determining the volume fractions of ferrite and austenite in the microstructure will be described later.
[0079] [Fn2] The duplex stainless steel material according to the present embodiment has the above-mentioned chemical composition, Fn1 is 40.0 or more, and the total number density ND of specific inclusions is 0.50 pieces / mm 2 or less, has a microstructure consisting of ferrite and austenite, and further has a total number density NDA (number / mm 2 ) and the total number density of specific inclusions in austenite (NDG (pieces / mm 2 ) satisfies the following formula (2). NDA / NDG<0.50 (2)
[0080] Fn2 (=NDA / NDG) is an index showing the extent to which specific inclusions (coarse Mn sulfides and coarse Ca sulfides) are present in ferrite. Between ferrite and austenite, austenite has better corrosion resistance than ferrite. Therefore, in duplex stainless steel materials having the above-mentioned chemical composition, there is a concern that pitting corrosion may occur selectively in ferrite.
[0081] On the other hand, if Fn2 is less than 0.50, the number density of specific inclusions in ferrite can be sufficiently reduced. As a result, the occurrence of selective pitting corrosion in ferrite can be suppressed, provided that the other configurations of this embodiment are satisfied. Therefore, in this embodiment, Fn2 is reduced to less than 0.50. As a result, the duplex stainless steel material has excellent general corrosion resistance and pitting corrosion resistance even in a supercritical corrosion environment, provided that the other configurations of this embodiment are satisfied.
[0082] As described above, the duplex stainless steel material according to this embodiment has a microstructure in which the volume fraction of ferrite and austenite is, for example, 35 to 65%. In this case, if Fn2 is less than 0.50, the number of specific inclusions in ferrite is smaller than the number of specific inclusions in austenite. Therefore, the pitting corrosion resistance of ferrite can be stably improved.
[0083] The upper limit of Fn2 is preferably 0.49, more preferably 0.48, and even more preferably 0.47. The lower limit of Fn2 is not particularly limited and may be 0.00. In the duplex stainless steel material according to this embodiment, the lower limit of Fn2 may be 0.01, 0.05, 0.10, or 0.15.
[0084] In this embodiment, the total number density ND (pieces / mm 2), the volume fraction (%) of ferrite and austenite in the microstructure, and Fn2 can be obtained by the following method. Specifically, a test piece for microstructure observation is prepared from the duplex stainless steel material according to this embodiment, and the volume fraction (%) of ferrite and austenite, the number density of coarse Mn sulfides and coarse Ca sulfides are obtained. More specifically, when the steel material is a steel plate, a test piece having an observation surface including the rolling direction and the plate thickness direction is prepared from the plate thickness center. When the steel material is a steel pipe, a test piece having an observation surface including the pipe axial direction and the pipe radial direction (wall thickness direction) is prepared from the wall thickness center. When the steel material is a round steel, a test piece having an observation surface including the axial direction and the radial direction is prepared from the R / 2 position in a cross section perpendicular to the axial direction of the round steel. In this specification, the R / 2 position of the round steel means the center position of the radius R in a cross section perpendicular to the axial direction of the round steel.
[0085] The observation surface of the prepared test piece is mirror-polished. The mirror-polished observation surface is etched in a mixture of aqua regia and glycerin to reveal the structure. The observation surface with the revealed structure is observed in 10 fields of view using an optical microscope. The area of each field of view is, for example, 2000 μm 2 (magnification 500x). In each field of view, ferrite and austenite are identified from the contrast. The area ratio of the identified ferrite is measured by a point counting method in accordance with JIS G0555 (2020). In this embodiment, the arithmetic average value of the area ratio of ferrite obtained in 10 fields of view is defined as the volume ratio of ferrite (%). The volume ratio of ferrite (%) is calculated by rounding off the obtained value to the first decimal place. The volume ratio of austenite (%) is calculated by subtracting the obtained volume ratio of ferrite (%) from 100.
[0086] Furthermore, particles in each field of view are identified from the contrast. An element concentration analysis (EDS analysis) is performed on each identified particle. In the EDS analysis, the acceleration voltage is set to 20 kV, and the target elements are quantified as N, O, Mg, Al, Si, P, S, Ca, Ti, Cr, Mn, Fe, Cu, Zr, and Nb. Based on the EDS analysis results of each particle, particles with a Mn content of 10 mass% or more and a S content of 10 mass% or more are identified as "Mn sulfides" when the total content of N, O, Mg, Al, Si, P, S, Ca, Ti, Cr, Mn, Fe, Cu, Zr, and Nb is taken as 100 mass%. Similarly, based on the EDS analysis results of each particle, particles having a Ca content of 20 mass% or more, an S content of 10 mass% or more, and an Mn content of less than 10 mass%, where the total content of N, O, Mg, Al, Si, P, S, Ca, Ti, Cr, Mn, Fe, Cu, Zr, and Nb is taken as 100 mass%, are identified as "Ca sulfides".
[0087] Among the Mn sulfides in each field of view, Mn sulfides with a circle equivalent diameter of 1.0 μm or more are specified as "coarse Mn sulfides". In other words, in this specification, "coarse Mn sulfides" means particles with a circle equivalent diameter of 1.0 μm or more, and with a Mn content of 10 mass% or more and a S content of 10 mass% or more when the total content of N, O, Mg, Al, Si, P, S, Ca, Ti, Cr, Mn, Fe, Cu, Zr, and Nb is defined as 100 mass%. Similarly, among the Ca sulfides in each field of view, Ca sulfides with a circle equivalent diameter of 2.0 μm or more are specified as "coarse Ca sulfides". In other words, in this specification, "coarse Ca sulfides" refers to particles having an equivalent circle diameter of 2.0 μm or more, and when the total content of N, O, Mg, Al, Si, P, S, Ca, Ti, Cr, Mn, Fe, Cu, Zr, and Nb is defined as 100 mass%, the Ca content is 20 mass% or more, the S content is 10 mass% or more, and the Mn content is less than 10 mass%.
[0088] The coarse Mn sulfides and coarse Ca sulfides identified by the above method are counted as "specific inclusions" in each field of view. Furthermore, the specific inclusions contained in the ferrite in each field of view are counted. Similarly, the specific inclusions contained in the austenite in each field of view are counted. As described above, the ferrite and austenite can be identified from the contrast in each field of view.
[0089] Based on the total number of specific inclusions counted in 10 visual fields and the total area of the 10 visual fields, the total number density ND (pieces / mm 2 Based on the total number of specific inclusions in the ferrite counted in 10 visual fields and the total area of the ferrite in 10 visual fields, the total number density NDA (number / mm 2 Based on the total number of specific inclusions in the austenite counted in 10 visual fields and the total area of the austenite in the 10 visual fields, the total number density NDG (number / mm 2 ) is calculated. Using the total number density NDA of the specific inclusions in the ferrite and the total number density NDG of the specific inclusions in the austenite, Fn2 (=NDA / NDG) is calculated.
[0090] The volume fraction of ferrite and austenite is calculated by rounding off the obtained value to the first decimal place. 2 ), the total number density of specific inclusions in the ferrite (NDA (pieces / mm 2 ), the total number density of specific inclusions in austenite (NDG (pieces / mm 2 ), and Fn2 are calculated by rounding the obtained numbers to two decimal places.
[0091] [General corrosion resistance and pitting corrosion resistance] The duplex stainless steel material according to the present embodiment has the above-mentioned chemical composition, Fn1 is 40.0 or more, and the total number density ND of specific inclusions is 0.50 pieces / mm 2or less, has a microstructure consisting of ferrite and austenite, and Fn2 is less than 0.50. As a result, the duplex stainless steel material according to this embodiment has excellent general corrosion resistance and pitting corrosion resistance even in a supercritical corrosion environment. In this embodiment, excellent general corrosion resistance and pitting corrosion resistance in a supercritical corrosion environment are evaluated by the following method.
[0092] Specifically, a test piece for a corrosion test is prepared from the duplex stainless steel material according to this embodiment. When the steel material is a steel pipe, the test piece is prepared from the center position of the wall thickness. In this case, the longitudinal direction of the test piece is parallel to the axial direction of the steel pipe. When the steel material is a round bar, the test piece is prepared from the R / 2 position. In this case, the longitudinal direction of the test piece is parallel to the axial direction of the round bar. When the steel material is a steel plate, the test piece is prepared from the center position of the plate thickness. In this case, the longitudinal direction of the test piece is parallel to the rolling direction of the steel plate. The test piece is, for example, 30 mm long, 20 mm wide, and 2 mm thick.
[0093] The test specimen is placed in the autoclave, and a 5.0 mass% sodium chloride aqueous solution saturated with 0.01 volume% SO2 gas and 0.05 volume% O2 gas is poured in so that the test specimen is immersed. The autoclave is filled with pressurized CO2 gas at a total pressure of 130 bar, and the corrosion test is started. The test time for the corrosion test is 96 hours, and the temperature inside the autoclave is maintained at 100°C during the test.
[0094] The mass, density, and surface area of the test piece after 96 hours are obtained, and the corrosion rate (mm / year) of the test piece is obtained. In this embodiment, the corrosion rate is obtained by rounding off the obtained value to the fourth decimal place. Furthermore, the surface of the test piece after 96 hours is observed with a magnifying glass with a magnification of 10 times to confirm the presence or absence of pitting corrosion. If the occurrence of pitting corrosion is suspected by the observation with the magnifying glass, the presence or absence of pitting corrosion is further confirmed by observation with an optical microscope with a magnification of 100 times. In this embodiment, if the corrosion rate obtained as a result of the corrosion test under the above conditions is 0.100 mm / year or less, it is evaluated as having excellent general corrosion resistance even in a supercritical corrosion environment. In this embodiment, if the corrosion test under the above conditions does not confirm pitting corrosion, it is evaluated as having excellent pitting corrosion resistance even in a supercritical corrosion environment.
[0095] [Yield strength] The yield strength of the duplex stainless steel material according to this embodiment is not particularly limited. The yield strength of the duplex stainless steel material according to this embodiment is, for example, 413 to 1035 MPa. In this embodiment, the lower limit of the yield strength of the duplex stainless steel material may be 427 MPa, 441 MPa, or 448 MPa. In this embodiment, the upper limit of the yield strength of the duplex stainless steel material may be 1020 MPa, 1007 MPa, or 1000 MPa.
[0096] The yield strength of the duplex stainless steel material according to this embodiment can be determined by the following method. Specifically, a tensile test is performed according to ASTM E8 / E8M(2022). A test piece is prepared from the steel material according to this embodiment. When the steel material is a steel plate, a round bar-shaped tensile test piece is prepared from the center of the plate thickness. In this case, the longitudinal direction of the tensile test piece is parallel to the rolling direction of the steel plate. When the steel material is a steel pipe, a round bar-shaped tensile test piece or an arc-shaped tensile test piece is prepared from the center of the wall thickness. In this case, the longitudinal direction of the tensile test piece is parallel to the pipe axis direction of the steel pipe. When the steel material is a round steel, a round bar-shaped tensile test piece is prepared from the R / 2 position. In this case, the longitudinal direction of the tensile test piece is parallel to the axial direction of the round steel.
[0097] The size of the round bar tensile test piece is, for example, 6.35 mm in parallel diameter and 25.4 mm in gauge length. The size of the arc tensile test piece is, for example, the total thickness, 25.4 mm in width, and 50.8 mm in gauge length. Using the prepared test piece, a tensile test is performed at room temperature (25°C) in air in accordance with ASTM E8 / E8M (2022). In this embodiment, the 0.2% offset yield strength obtained from the tensile test is defined as the yield strength (MPa). In this embodiment, the yield strength (MPa) is obtained by rounding off the obtained numerical value to the nearest tenth.
[0098] [Shape of duplex stainless steel material] As described above, the shape of the duplex stainless steel material according to the present embodiment is not particularly limited. The duplex stainless steel material according to the present embodiment may be, for example, a steel pipe, a steel plate, a round bar, or a wire rod. Preferably, the duplex stainless steel material according to the present embodiment is a seamless steel pipe. When the duplex stainless steel material according to the present embodiment is a seamless steel pipe, it has excellent general corrosion resistance and pitting corrosion resistance in a supercritical corrosion environment even if the wall thickness is 5 mm or more.
[0099] [Manufacturing method] An example of a method for producing a duplex stainless steel material according to the present embodiment having the above-mentioned configuration will be described. Note that the method for producing a duplex stainless steel material according to the present embodiment is not limited to the method described below. The example of a method for producing a duplex stainless steel material according to the present embodiment includes a steelmaking process, a hot working process, and a solution treatment process. Each of the manufacturing processes will be described in detail below.
[0100] [Steel manufacturing process] The steelmaking process according to the present embodiment includes a step of producing molten steel (refining step) and a step of producing a material by casting using the molten steel (material production step). Each step will be described below.
[0101] [Refining process] In the refining process, molten steel containing Cr is first placed in a ladle, and the molten steel in the ladle is subjected to a decarburization process under atmospheric pressure. This process is called a rough decarburization refining process. Slag is generated by the decarburization process in the rough decarburization refining process. The slag generated by the decarburization process floats on the liquid surface of the molten steel after the rough decarburization refining process. In the rough decarburization refining process, Cr in the molten steel is oxidized to generate Cr2O3. Cr2O3 is absorbed in the slag. Therefore, a deoxidizer is added to the ladle to reduce the Cr2O3 in the slag, and Cr is recovered in the molten steel. This process is called a Cr reduction process. The rough decarburization refining process and the Cr reduction process are carried out, for example, by an electric furnace process, a converter process, or an AOD (Argon Oxygen Decarburization) process. After the Cr reduction process, the slag is removed from the molten steel. This process is called a slag removal process.
[0102] In the case of Cr-containing steel, the C activity is reduced by Cr, which inhibits the decarburization reaction. Therefore, a final decarburization process is carried out on the molten steel after the slag removal process. This process is called the final decarburization refining process. In the final decarburization refining process, the decarburization process is carried out under reduced pressure. If the decarburization process is carried out under reduced pressure, the partial pressure of CO gas in the atmosphere (P CO ) is lowered, suppressing the oxidation of Cr in the molten steel. Therefore, if the decarburization process is performed under reduced pressure, the C concentration in the molten steel can be further reduced while suppressing the oxidation of Cr. After the final decarburization refining process, a deoxidizer is added to the molten steel and a Cr reduction process is performed again to reduce the Cr2O3 in the slag. This process is called the Cr reduction process. The final decarburization refining process and the Cr reduction process after the final decarburization refining process may be performed by, for example, the VOD (Vacuum Oxygen Decarburization) method or the RH (Ruhrstahl-Heraeus) method.
[0103] After the Cr reduction treatment process, the molten steel in the ladle is subjected to final composition adjustment and temperature adjustment before the material manufacturing process. This process is called the composition adjustment process. The composition adjustment process is carried out, for example, by ladle treatment (LT). In the latter half of the composition adjustment process, Ca is added to the molten steel. Here, the time from when Ca is added until Ca is uniformly dispersed in the molten steel is defined as the "uniform mixing time τ". The uniform mixing time τ can be calculated by the following formula (A). τ=800×ε -0.4 (A) Here, ε is the stirring power density of the molten steel in the LT and is defined by equation (B). ε=28.5(Q / W)×T×log(1+H / 1.48) (B) Here, Q is the top blown gas flow rate (Nm 3 / min). W is the mass of molten steel (t). T is the temperature of molten steel (K). H is the depth of the molten steel in the ladle (steel bath depth) (m).
[0104] In the composition adjustment step, the temperature of the molten steel in the ladle is maintained at 1500 to 1700°C. Furthermore, Ca is added to the molten steel, and the holding time after the uniform mixing time τ has elapsed is defined as "holding time t" (seconds). In this embodiment, the holding time t after the uniform mixing time τ has elapsed is preferably 60 seconds or more.
[0105] If the holding time t is too short, Ca may not be able to sufficiently modify Mn sulfides in the molten steel. In this case, a large number of coarse Mn sulfides remain in the steel. As a result, the number density of the specific inclusions in the produced duplex stainless steel material becomes too high. Therefore, in the refining process according to this embodiment, it is preferable to set the holding time t after the uniform mixing time τ has elapsed to 60 seconds or more.
[0106] As described above, in the refining step of this embodiment, the holding time t after the uniform mixing time τ in the composition adjustment step is set to 60 seconds or more. Note that, in the composition adjustment step of this embodiment, the upper limit of the holding time t after the uniform mixing time τ has elapsed is not particularly limited, but is, for example, 3600 seconds.
[0107] [Material manufacturing process] The molten steel produced by the above-mentioned refining process is used to produce a material. The material is a cast piece or an ingot. Specifically, the molten steel is used to produce a cast piece by a continuous casting method. The cast piece may be a slab, a bloom, or a billet. Alternatively, the molten steel may be used to produce an ingot by an ingot casting method. The cast piece or the ingot may be further subjected to blooming or the like to produce a billet.
[0108] In the duplex stainless steel material having the above-mentioned chemical composition, austenite is generated during solidification of molten steel, and the temperature range in which the generated austenite grows is 1350 to 1100°C. Therefore, in this embodiment, the cooling rate at 1350 to 1100°C is controlled to unevenly distribute the specific inclusions in the austenite. Specifically, if the cooling rate of the material at 1350 to 1100°C is slower than usual, austenite nucleates and grows preferentially from the vicinity of the inclusions, so that the austenite easily takes in the inclusions.
[0109] On the other hand, if the cooling rate of the material at 1350 to 1100°C is too fast, the material will be in an overcooled state, and the generation and growth of austenite will tend to occur randomly. As a result, in the manufactured duplex stainless steel material, the specific inclusions will not easily be unevenly distributed in the austenite, and Fn2 may be 0.50 or more. On the other hand, if the cooling rate of the material at a temperature of 1350 to 1100°C is too slow, the austenite will tend to coarsen. As a result, the manufactured duplex stainless steel material may not have the desired mechanical properties.
[0110] Therefore, in the material manufacturing process according to this embodiment, the cooling rate when the material temperature is 1350 to 1100°C is preferably 8.0 to 25.0°C / min. The method for controlling the cooling rate when the material temperature is 1350 to 1100°C is not particularly limited, and any well-known method may be used. For example, when manufacturing the material by continuous casting, the cooling rate can be controlled by adjusting the amount of cooling water (specific water amount) that cools the slab. For example, when manufacturing the material by ingot casting, the cooling rate can be controlled by the material of the mold or water cooling of the mold.
[0111] Here, it is difficult to measure the internal temperature of the material in practical operation. In addition, in this embodiment, since the material is cooled in a steady state, the cooling rate based on the surface temperature of the material is equivalent to the cooling rate inside the material. More specifically, in the material of this embodiment, it was confirmed that the cooling rate when the internal temperature of the material is 1350 to 1100°C is equivalent to the cooling rate when the surface temperature of the material is 1200 to 950°C. Therefore, in the material manufacturing process of this embodiment, if the internal temperature of the material cannot be controlled, it is preferable to set the cooling rate when the surface temperature of the material is 1200 to 950°C to 8.0 to 25.0°C / min. The surface temperature of the material can be measured by a non-contact infrared thermometer. The material is manufactured by the above process.
[0112] [Hot processing process] In the hot working process according to this embodiment, the material prepared in the steelmaking process is hot worked to produce an intermediate steel material. In this specification, the intermediate steel material refers to a plate-shaped steel material when the final product is a steel plate, a blank pipe when the final product is a steel pipe, a steel material with a circular cross section when the final product is a round bar, and a wire-shaped steel material when the final product is a wire rod. The hot working may be hot forging, hot extrusion, or hot rolling. The method of hot working is not particularly limited and may be a well-known method.
[0113] When the intermediate steel material is a mother pipe (seamless steel pipe), for example, the Eugène-Sejournet method or the Erhardt push bench method (i.e., hot extrusion) may be performed in the hot working step, or piercing and rolling by the Mannesmann method (i.e., hot rolling) may be performed. The hot working may be performed only once or multiple times. For example, the above-mentioned piercing and rolling may be performed on the material, and then the above-mentioned hot extrusion may be performed. For example, the above-mentioned piercing and rolling may be performed on the material, and then the elongation rolling may be performed. That is, in the hot working step, hot working is performed by a well-known method to manufacture a mother pipe. The heating temperature of the material during the hot working is, for example, 1000 to 1280°C.
[0114] In addition, when the steel material is round steel or steel plate, the intermediate steel material may be manufactured as follows. When the steel material is round steel, the material is first heated in a heating furnace. The heating temperature is not particularly limited, but is, for example, 1000 to 1280°C. The material extracted from the heating furnace is subjected to hot processing to manufacture an intermediate steel material having a circular cross section perpendicular to the axial direction. The hot processing is, for example, blooming rolling by a blooming mill, or hot rolling by a continuous rolling mill. In the continuous rolling mill, a horizontal stand having a pair of grooved rolls arranged side by side in the vertical direction and a vertical stand having a pair of grooved rolls arranged side by side in the horizontal direction are alternately arranged.
[0115] When the steel material is a steel plate, the material is first heated in a heating furnace. The heating temperature is not particularly limited, but is, for example, 1000 to 1280° C. The material removed from the heating furnace is subjected to hot rolling using a blooming mill and a continuous rolling mill to produce an intermediate steel material in the shape of a steel plate.
[0116] [Solution treatment process] In the solution treatment process, the intermediate steel material is subjected to solution treatment. The method of solution treatment is not particularly limited and may be a well-known method. For example, the intermediate steel material is charged into a heat treatment furnace, held at a desired temperature, and then quenched. When the intermediate steel material is charged into a heat treatment furnace, held at a desired temperature, and then quenched to perform solution treatment, the solution temperature means the temperature (°C) of the heat treatment furnace for performing the solution treatment. In this case, the solution time means the time during which the intermediate steel material is held at the solution temperature.
[0117] Preferably, the solution treatment temperature in the solution treatment step of this embodiment is 900 to 1200° C. If the solution treatment temperature is too low, precipitates (e.g., σ-phase, which is an intermetallic compound) may remain in the intermediate steel material after the solution treatment, which may result in a decrease in corrosion resistance of the produced duplex stainless steel material.
[0118] When the intermediate steel material is charged into a heat treatment furnace, held at a desired temperature, and then rapidly cooled to perform solution treatment, the solution treatment time is not particularly limited and may be performed under well-known conditions. The solution treatment time is, for example, 5 to 180 minutes. The rapid cooling method is, for example, water cooling.
[0119] [Other processes] If necessary, the duplex stainless steel material that has been subjected to the solution treatment may be subjected to pickling treatment. In this case, the pickling treatment may be performed by a well-known method, and is not particularly limited. The duplex stainless steel material that has been subjected to the solution treatment may be subjected to cold working. When cold working is performed, the strength of the duplex stainless steel material can be increased. Even when cold working is performed, the duplex stainless steel material has the above-mentioned chemical composition, Fn1 is 40.0 or more, and the total number density ND of the specific inclusions is 0.50 pieces / mm 2 A duplex stainless steel material having a microstructure consisting of ferrite and austenite and having an Fn2 of less than 0.50 has excellent general corrosion resistance and pitting corrosion resistance even in a supercritical corrosion environment.
[0120] The duplex stainless steel material according to this embodiment can be manufactured by the above steps. The above-mentioned method for manufacturing the duplex stainless steel material is one example, and the duplex stainless steel material according to this embodiment may be manufactured by other methods. The duplex stainless steel material according to this embodiment will be described in more detail below by way of an example. The example described below is an example of one condition adopted to confirm the feasibility and effects of the duplex stainless steel material according to this embodiment. In other words, the duplex stainless steel material according to this embodiment is not limited to the example described below. EXAMPLES
[0121] Duplex stainless steel materials (seamless steel pipes) having the chemical compositions shown in Tables 1-1 to 1-3 were manufactured by the following method. In Tables 1-1 to 1-3, "-" in the "Chemical composition" column means that the corresponding element content is 0% in the numerical values up to the lowest digit described in the embodiment. Specifically, the Mg content, REM content, Zr content, Nb content, Ta content, As content, Zn content, Pb content, and Sb content of Test No. 1 were 0% when rounded off to the fourth decimal place.
[0122] [Table 1-1]
[0123] [Table 1-2]
[0124] [Table 1-3]
[0125] Molten steel for each test number was produced as follows. Molten steel containing Cr was placed in a ladle, and a well-known rough decarburization refining process and Cr reduction treatment process were carried out by the AOD process. After the Cr reduction treatment process, a slag removal process was carried out to remove slag from the molten steel. Furthermore, a well-known finish decarburization refining process and Cr reduction treatment process were carried out by the VOD process.
[0126] After the Cr reduction process by the VOD method, the molten steel in the ladle was subjected to final composition adjustment and temperature adjustment before the material production process by LT. The molten steel temperature was 1500 to 1700°C in all cases. Furthermore, Ca was added to the molten steel. After Ca was added, the holding time t (seconds) after the uniform mixing time τ had elapsed was adjusted as shown in Table 2. The molten steel with each test number was produced by the above process.
[0127] [Table 2]
[0128] The produced molten steel was used to produce a billet by continuous casting. When producing the billet, the cooling rate at which the billet temperature was 1350-1100°C was adjusted as shown in "Cooling rate at 1350-1100°C (°C / min)" in Table 2. The cooling rate was adjusted by adjusting the specific water amount. Since it was difficult to measure the internal temperature of the billet, in this example, the cooling rate at which the billet surface temperature was 1200-950°C was measured and considered to be the cooling rate at which the billet internal temperature was 1350-1100°C. The surface temperature of the billet was also measured using an infrared radiation thermometer.
[0129] The produced billet was heated to 1250°C and then hot rolled by the Mannesmann process to produce a mother pipe (seamless steel pipe) with an outer diameter of 244.48 mm and a wall thickness of 13.84 mm. Furthermore, the mother pipe was subjected to a solution treatment. The solution treatment temperature was 1080°C, and the solution treatment time was 15 minutes. After the solution treatment time had elapsed, the mother pipe was water-cooled. The water-cooled seamless steel pipes of test numbers 21 to 27 were further subjected to cold working. In this example, cold drawing was performed as the cold working. Through the above steps, the steel material (seamless steel pipe) of each test number was produced.
[0130] [Evaluation test] The steel materials with each test number were subjected to a microstructure observation test, a tensile test, and a corrosion test. Note that the steel material with test number 41 was not subjected to any evaluation test because it had defects during the manufacturing process.
[0131] [Microstructure observation test] For each steel material with a test number other than test number 41, a microstructure observation test was carried out to identify the microstructure, and the total number density ND (number / mm 2 ) and Fn2 were obtained. Specifically, a test piece for microstructure observation was prepared and the microstructure was identified by the above-mentioned method. Furthermore, the total number density ND of the specific inclusions was obtained by the above-mentioned method. Furthermore, Fn2 was obtained by the above-mentioned method. The area of each field of view was 2000 μm 2 (magnification: 500x).
[0132] All of the steels with test numbers except test number 41 had a microstructure consisting of ferrite and austenite. Furthermore, the volume fraction of ferrite was within the range of 35 to 65%. In addition, the total number density ND (number / mm 2 ) in Table 2, "Total number density ND (pieces / mm 2 In addition, the total number density NDA (pieces / mm 2 ) and the total number density of specific inclusions in austenite (NDG (pieces / mm 2) and Fn2 (=NDA / NDG) was calculated. The obtained Fn2 is shown in Table 2. As mentioned above, the microstructure observation test was not performed for test number 41, and therefore "-" (no evaluation) is shown in Table 2.
[0133] [Tensile test] A tensile test was performed on the steel material of each test number except for test number 41 in accordance with ASTM E8 / E8M (2022) to determine the yield strength. Specifically, an arc-shaped tensile test piece was prepared for the tensile test by the above-mentioned method. The arc-shaped tensile test piece had the same thickness as the wall thickness of the seamless steel pipe, a width of 25.4 mm, and a gauge length of 50.8 mm. A tensile test was performed using the tensile test piece of each test number at room temperature (25°C) in the air to determine the 0.2% offset yield strength (MPa). The determined 0.2% offset yield strength was defined as the yield strength (MPa). The yield strength (Yield Strength) of each test number obtained is shown in the "YS (MPa)" column of Table 2. Note that the yield strength of all the steel materials of each test number except for test number 41 was 413 to 1035 MPa. As described above, the tensile test was not performed for test number 41, and therefore the test number is shown in Table 2 as "-" (no evaluation).
[0134] [Corrosion test] A corrosion test was carried out on the steel material of each test number except for test number 41, and the general corrosion resistance and pitting corrosion resistance in a supercritical corrosion environment were evaluated. Specifically, a test piece for the corrosion test was prepared by the above-mentioned method. A corrosion test was carried out on the prepared test piece under the above-mentioned conditions to obtain the corrosion rate (mm / year). Furthermore, the presence or absence of pitting corrosion was confirmed for the test piece after the corrosion test by the above-mentioned method. The obtained corrosion rates (mm / year) are shown in Table 2. Furthermore, the test numbers in which pitting corrosion was not confirmed are indicated as "E (Excellent)" in the "Pitting Corrosion" column of Table 2. Furthermore, the test numbers in which pitting corrosion was confirmed are indicated as "NA (Not Acceptable)" in the "Pitting Corrosion" column of Table 2. As mentioned above, the corrosion test was not carried out on test number 41, so "-" (no evaluation) is shown in Table 2.
[0135] [Evaluation Results] With reference to Tables 1-1, 1-2, 1-3, and 2, the duplex stainless steel materials of test numbers 1 to 27 had appropriate chemical compositions, Fn1 was 40.0 or more, and the manufacturing method also satisfied the conditions of the above-mentioned preferred manufacturing method. Furthermore, these steel materials have a microstructure consisting of ferrite and austenite, and the total number density ND of specific inclusions is 0.50 pieces / mm 2 The corrosion rates of these steel materials were 0.100 mm / year or less, and Fn2 was less than 0.50. As a result, the corrosion rates of these steel materials were 0.100 mm / year or less, and no pitting corrosion was observed. In other words, these steel materials had excellent general corrosion resistance and pitting corrosion resistance even in a supercritical corrosion environment.
[0136] On the other hand, the Cr content of the steel material of test number 28 was too low. As a result, the corrosion rate of this steel material exceeded 0.100 mm / year. In other words, this steel material did not have excellent general corrosion resistance in a supercritical corrosion environment.
[0137] The steel material of test number 29 had too low a Cu content, and as a result, the corrosion rate of this steel material exceeded 0.100 mm / year, which means that this steel material did not have excellent general corrosion resistance in a supercritical corrosion environment.
[0138] The steel material of test number 30 had a too low W content. As a result, the corrosion rate of this steel material exceeded 0.100 mm / year. In other words, this steel material did not have excellent general corrosion resistance in a supercritical corrosion environment.
[0139] The steel material of test number 31 had too low a Co content. As a result, pitting corrosion was confirmed in the corrosion test. That is, this steel material did not have excellent pitting corrosion resistance in a supercritical corrosion environment.
[0140] The steel material of test number 32 had too low an Sn content, and as a result, pitting corrosion was confirmed in the corrosion test, meaning that the steel material did not have excellent pitting corrosion resistance in a supercritical corrosion environment.
[0141] The steel material of test number 33 had too high an Al content. Furthermore, this steel material had a total number density ND of specific inclusions of 0.50 pieces / mm 2 As a result, pitting corrosion was confirmed in the corrosion test of this steel material, which means that this steel material does not have excellent pitting corrosion resistance in a supercritical corrosion environment.
[0142] The steel material of test number 34 had too low a Ca content. Furthermore, the total number density ND of specific inclusions in this steel material was 0.50 pieces / mm 2 As a result, pitting corrosion was confirmed in the corrosion test of this steel material, which means that this steel material does not have excellent pitting corrosion resistance in a supercritical corrosion environment.
[0143] The steel materials of test numbers 35 to 37 had too low Fn1. As a result, the corrosion rates of these steel materials exceeded 0.100 mm / year. In other words, these steel materials did not have excellent general corrosion resistance in a supercritical corrosion environment.
[0144] In the steels of test numbers 38 to 40, the holding time t after the uniform mixing time τ had elapsed after adding Ca was too short. Furthermore, in these steels, the total number density ND of specific inclusions was 0.50 pieces / mm 2 As a result, pitting corrosion was confirmed in the corrosion test of these steel materials, which means that these steel materials did not have excellent pitting corrosion resistance in a supercritical corrosion environment.
[0145] As mentioned above, the steel material of test number 41 had defects that occurred during the manufacturing process.
[0146] The steel material of test number 42 had a too fast cooling rate at 1350 to 1100°C. Furthermore, this steel material had an Fn2 of 0.50 or more. As a result, pitting corrosion was confirmed in the corrosion test for this steel material. In other words, this steel material did not have excellent pitting corrosion resistance in a supercritical corrosion environment.
[0147] The embodiments of the present disclosure have been described above. However, the above-described embodiments are merely examples for implementing the present disclosure. Therefore, the present disclosure is not limited to the above-described embodiments, and can be implemented by appropriately modifying the above-described embodiments without departing from the spirit of the present disclosure.
Claims
1. A duplex stainless steel material, In mass percent, C: 0.050% or less, Si: 1.00% or less, Mn: 0.40-3.00%, P: 0.050% or less, S: 0.0050% or less, Cr: 20.00-24.50%, Cu: 0.10-3.00%, Ni: 2.00-10.00%, Mo: 0.80-5.00%, W: 0.01-1.50%, N: 0.001-0.350%, Co: 0.10-1.00%, Sn: 0.001 to 0.050%, sol. Al: 0.050% or less, V: 0.01-0.50%, Ti: 0.001 to 0.050%, Ca: 0.0005-0.0100%, B: 0.0015-0.0050%, O: 0.010% or less, Mg: 0 to 0.010%, Rare earth elements: 0 to 0.010%, Zr: 0 to 0.010%, Nb: 0 to 0.500%, Ta: 0-0.100%, As: 0 to 0.050%, Zn: 0 to 0.010%, Pb: 0 to 0.010%, Sb: 0 to 0.010%, and The balance is Fe and impurities, Assuming that the content of each of the elements is within the above-mentioned range, Fn1 defined by formula (1) is 40.0 or more, In the duplex stainless steel material, Particles having a circle equivalent diameter of 1.0 μm or more, a Mn content of 10 mass% or more, and a S content of 10 mass% or more are defined as coarse Mn sulfides, When particles having a circle equivalent diameter of 2.0 μm or more, a Ca content of 20 mass% or more, an S content of 10 mass% or more, and an Mn content of less than 10 mass% are defined as coarse Ca sulfides, The total density of the coarse Mn sulfides and the coarse Ca sulfides is 0.50 particles / mm 2 is as follows: The microstructure of the duplex stainless steel material is composed of ferrite and austenite, The total number density of the coarse Mn sulfides and the coarse Ca sulfides in the ferrite is expressed as NDA pieces / mm 2 Define it as: The total number density of the coarse Mn sulfides and the coarse Ca sulfides in the austenite is defined as NDG pieces / mm 2 When we define The NDA and the NDG satisfy formula (2); Duplex stainless steel material. Fn1=Cr+3.3(Mo+0.5W)+16N+2Ni+Cu+2Co+10Sn (1) NDA / NDG<0.50 (2) Here, the element symbols in formula (1) are substituted with the contents of the corresponding elements in mass %.
2. 2. The duplex stainless steel material according to claim 1, Mg: 0.001-0.010%, Rare earth elements: 0.001 to 0.010%, Zr: 0.001 to 0.010%, Nb: 0.001-0.500%, Ta: 0.001 to 0.100%, As: 0.001 to 0.050%, Zn: 0.001-0.010%, Pb: 0.001 to 0.010%, and Sb: 0.001 to 0.010%; containing one or more elements selected from the group consisting of: Duplex stainless steel material.
3. The duplex stainless steel material according to claim 1 or 2, The duplex stainless steel material is a steel pipe. Duplex stainless steel material.
Citation Information
Patent Citations
Two-phase stainless steel material, two-phase stainless steel pipe and surface treatment method for two-phase stainless steel material
JP2016216816A
Ferrite-austenite two-phase system stainless steel material and method for manufacturing them, and corrosion-resistant member
JP2022155339A
Ferrite-austenite two-phase system stainless steel material and method for manufacturing the same, and corrosion-resistant member
JP2022155343A
Duplex stainless steel material
WO2023058630A1
Duplex stainless steel material
WO2023058631A1